Spectrophotometric determination of cefaclor in pharmaceutical preparations - Ivama, Viviane M. [UNESP]; Rodrigues, Letícia N. C. [UNESP]; Guaratini, Cláudia C. I. [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Sociedade Brasileira de Química, 1999)
A simple spectrophotometric method is proposed for the determination of cefaclor. The method involves alkaline hydrolysis of the drug in ammonia buffer solution at pH 10 to yield diketopiperazine-2,5-dione derivative and subsequent measurement at 340 nm. Beer's law is obeyed in the concentration range 1.8 - 55 mg/mL. The proposed method was successfully applied to the determination of cefaclor in pharmaceutical formulations.
Keywords: cefaclor; hydrolysis; pharmaceuticals